The Positive Impacts of Sustainability in the Community - Martins De Moraes, Thiago Matheus [UNESP]; Jacintho, Felipe Fernandes; Camargo, Gabriela Maia [UNESP]; Adami, Jose Feliciano [UNESP]; Dias, Rubens Alves [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The Brazilian electric power matrix has always been profoundly dependent on hydroelectric power plants. According to the 2019 decennial plan by the Energy Research Company (EPE, in Portuguese), 60% of the instal led power from Brazil's electrical system is in large hydroelectric plants, and 4% is in small hydroelectric plants. Recently, however, between 2014 and 2016, the most representative Brazilian federative unit, in terms of gross domestic product, suffered a severe hydroelectric crisis, which highlighted discussions about the future of power generation.